Polymer-augmented liposomes enhancing antibiotic delivery against intracellular infections. (31st May 2018) - Su, Fang-Yi; Chen, Jasmin; Son, Hye-Nam; Kelly, Abby M.; Convertine, Anthony J.; West, T. Eoin; Skerrett, Shawn J.; Ratner, Daniel M.; Stayton, Patrick S.
Abstract : A simplified liposome formulation with three functionalities to enhance antibiotic bioavailability to cytosolic bacteria: carbohydrate-mediated targeting; pH-responsive release; endosomal-release activity. Abstract : Pulmonary intracellular infections, such as tuberculosis, anthrax, and tularemia, have remained a significant challenge to conventional antibiotic therapy. Ineffective antibiotic treatment of these infections can lead not only to undesired side effects, but also to the emergence of antibiotic resistance. Aminoglycosides ( e.g., streptomycin) have long been part of the therapeutic regiment for many pulmonary intracellular infections. Their bioavailability for intracellular bacterial pools, however, is limited by poor membrane permeability and rapid elimination. To address this challenge, polymer-augmented liposomes (PALs) were developed to provide improved cytosolic delivery of streptomycin to alveolar macrophages, an important host cell for intracellular pathogens. A multifunctional diblock copolymer was engineered to functionalize PALs with carbohydrate-mediated targeting, pH-responsive drug release, and endosomal release activity with a single functional polymer that replaces the pegylated lipid component to simplify the liposome formulation. The pH-sensing functionality enabled PALs to provide enhanced release of streptomycin under endosomal pH conditions (70% release in 6 hours) with limited release at physiological pH 7.4 (16%). The membrane-destabilizing activity connected to endosomal release was characterized in a hemolysis assay and PALs displayed a sharp pH profile across the endosomal pH development target range. The direct connection of this membrane-destabilizing pH profile to model drug release was demonstrated in an established pyranine/ p -xylene bispyridinium dibromide (DPX) fluorescence dequenching assay. PALs displayed similar sharp pH-responsive release, whereas PEGylated control liposomes did not, and similar profiles were then shown for streptomycin release. The mannose-targeting capability of the PALs was also demonstrated with 2.5 times higher internalization compared to non-targeted PEGylated liposomes. Finally, the streptomycin-loaded PALs were shown to have a significantly improved intracellular antibacterial activity in a Francisella-macrophage co-culture model, compared with free streptomycin or streptomycin delivered by control PEGylated liposomes (13× and 16×, respectively). This study suggests the potential of PALs as a useful platform to deliver antibiotics for the treatment of intracellular macrophage infections.